Biosafety measures to prevent COVID-19 in healthcare professionals: an integrative review - Olvani Martins da Silva; Danielle Bezerra Cabral; Sandra Mara Marin; Julia Valeria de Oliveira Vargas Bitencourt; Mara Ambrosina de Oliveira Vargas; William Campo Meschial
ABSTRACT Objective: to identify the main biosafety measures for preventing COVID-19 in healthcare professionals. Methods: this is an integrative literature review, with studies published between January and July 2020, on the MEDLINE/PubMed, Scopus, Embase, Web of Science, LILACS, SciELo, Wiley Online Library, Cochrane CINAHL databases. The selection of studies followed the PRISMA recommendations. Results: among the 2,208 publications identified, 12 studies comprised the sample, which enabled the analysis in four thematic categories: The importance of using recommendations about the use of personal protective equipment; The restructuring of new operational and clinical routines and flows in the practice of services; Monitoring professionals, especially testing; Conducting training. Conclusions: the phenomena involved are innumerable, covering operational management and the training of teams to deal with highly infectious pathogens and disease outbreaks.